Building bridges : from Asian faiths to Jesus in the Gospels - Nicholls, Bruce (Regnum studies in mission., 2019)
"In an age of religious confrontation, rationalism and individualism, this book seeks to build bridges of mutual respect between Christians and Hindus, Sikhs, Buddhists and Muslims. They are encouraged to examine the truths in their scriptures and from their founders, in order to awaken their desire to read the Gospels and understand their sinful predicament. As they come to know who Jesus is and why he came, they are invited to accept his call to faith and discipleship. Special attention is given to the communicative power of poetry in the Asian context."--Publisher.